Project-Based Learning: Beyond a Means to Promote Language Skills - Aghayani, Behnam (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2024)
Considering the importance of project-based learning in EFL context, the present study first aims to review the studies that have investigated the effect of project-based learning on language skills in the last decade, while the second, using sociocultural theory as a theoretical framework, explores EFL learners’ attitudes toward project-based learning. In addition, the differences between female and male EFL learners’ attitudes toward project-based learning examined in this study. In order to reach this goal, a sample of 210 Iranian university EFL learners both female (n=150) and male (n=60) participated in this study. A project-based learning questionnaire was used to collect the required data using a 6-point Likert scale. The results revealed that EFL learners had positive attitude toward project-based learning. Moreover, based on the data analysis, there were no significant differences between female and male responses to the questionnaire items except two questions in which female learners were more positive than male learners. The results of the study could be of interest both to EFL teachers who want to engage their students in project-based learning and to researchers who seek to investigate on the effect of project-based learning among different genders.